Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcell.2022.901351
|View full text |Cite
|
Sign up to set email alerts
|

In Depth Exploration of the Alternative Proteome of Drosophila melanogaster

Abstract: Recent studies have shown that hundreds of small proteins were occulted when protein-coding genes were annotated. These proteins, called alternative proteins, have failed to be annotated notably due to the short length of their open reading frame (less than 100 codons) or the enforced rule establishing that messenger RNAs (mRNAs) are monocistronic. Several alternative proteins were shown to be biologically active molecules and seem to be involved in a wide range of biological functions. However, genome-wide ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…However, we found that a high proportion of predicted smORF peptides are located in the 5’UTR and 3’UTR, supporting the existence of polycistronic eukaryotic genes. Indeed, recent studies in Drosophila or vertebrates using mass spectrometry or ribosome profiling have shown that smORF peptides are indeed translated from the 5’ or 3’ UTR, even within the main ORF, demonstrating that polycistronic genes in eukaryotes are more widespread than expected (Chen et al, 2020; Fabre et al, 2022; Martinez et al, 2023). This highlights the potential of RNAs to code for several proteins, giving the possibility of greatly increasing the eukaryotic proteome.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that a high proportion of predicted smORF peptides are located in the 5’UTR and 3’UTR, supporting the existence of polycistronic eukaryotic genes. Indeed, recent studies in Drosophila or vertebrates using mass spectrometry or ribosome profiling have shown that smORF peptides are indeed translated from the 5’ or 3’ UTR, even within the main ORF, demonstrating that polycistronic genes in eukaryotes are more widespread than expected (Chen et al, 2020; Fabre et al, 2022; Martinez et al, 2023). This highlights the potential of RNAs to code for several proteins, giving the possibility of greatly increasing the eukaryotic proteome.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few elegant works using MS for AltProt detection have been reported in recent years, but the number of AltProt identified to our knowledge still varies widely, from tens ( 2 , 20 , 28 ) to hundreds ( 21 , 22 , 24 ). This is probably explained by the different enrichment and analysis methods used and the sample variation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, mass spectrometry (MS) is considered as the only method that allows direct identification of AltProts ( 18 , 19 ). However, only tens to hundreds of AltProts per sample can be identified by MS ( 2 , 20 , 21 , 22 ). The big difference in the identification number between the two methods calls for urgent improvement on the MS-based methodologies to detect AltProts.…”
mentioning
confidence: 99%
“…Frozen cells were lysed in a sodium dodecyl sulfate (SDS)-based buffer [34], sonicated and boiled for 5 min at 95 • C. BCA assay (Thermo Fisher Scientific, Waltham, MA, USA) was used to measure protein concentration in each sample. 5× Laemmli buffer was added to 50 µg of proteins and the samples were boiled for 5 min at 95 • C before loading on an SDS-PAGE gel (acrylamide concentration of 4% for the stacking gel and 12% for the resolving gel).…”
Section: Western Blot Analysismentioning
confidence: 99%